2005
DOI: 10.1007/s00421-005-0109-1
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization effects in young and older adults

Abstract: This experiment compared the effects of disuse on the adductor pollicis (AP) muscle in young (YM) and old (OM) men. The AP of the YM and OM was assessed for strength (MVC), compound muscle action potential (CMAP), and volume, and then immobilized for 2 weeks. MVC decreased approximately 22% in the YM, and OM (P<0.001). AP volume was 4.1% (not significant) and 9.5% (P<0.05) less in the YM and OM, respectively. CMAP increased in the OM 0, 24, and 48 h post-immobilization, and did not change in the YM. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 18 publications
3
45
0
1
Order By: Relevance
“…Studies on immobilization and unloading have underlined the fact that skeletal muscle tissue responds quickly to unloading with a lowering of muscle strength by approximately 10-22% after 2 weeks (Alfredson et al 1998;Berg and Tesch 1996;Urso et al 2006), and that longer periods of unloading decrease the muscle strength and cross-sectional area (CSA) even further (Christensen et al 2008;Stevens et al 2006). In addition to the muscle strength, neuromuscular functions have also shown impairment by immobilization (Clark et al 2006).…”
Section: Introductionmentioning
confidence: 96%
“…Studies on immobilization and unloading have underlined the fact that skeletal muscle tissue responds quickly to unloading with a lowering of muscle strength by approximately 10-22% after 2 weeks (Alfredson et al 1998;Berg and Tesch 1996;Urso et al 2006), and that longer periods of unloading decrease the muscle strength and cross-sectional area (CSA) even further (Christensen et al 2008;Stevens et al 2006). In addition to the muscle strength, neuromuscular functions have also shown impairment by immobilization (Clark et al 2006).…”
Section: Introductionmentioning
confidence: 96%
“…This is contrasted by the fact that the elderly population more often undergoes periods of immobilization and disuse, not only due to joint pain, but also due to a higher degree of comorbidity and hospitalization (32). Studies in healthy young adults have demonstrated that immobilization leads to rapid decreases in maximal muscle strength, muscle mass, and neural activation (4,19); however, recent studies indicate that skeletal muscle in aged animals and humans is more vulnerable to muscle unloading than that in young individuals (8,41). Furthermore, recent data from Yasuda et al (43) show that there might be a gender-specific response to unloading, as evidenced by a more pronounced decrease in specific strength in young women compared with young men after 14 days of unilateral limb immobilization.…”
mentioning
confidence: 99%
“…Fleck e Kraemer (1997) relatam que ocorre um decréscimo nos valores de repouso dos hormônios anabólicos como testosterona, hormônio do crescimento e insulina, bem como a resposta destes ao treinamento de força. Em estudo comparando idosos e jovens, Urso et al (2006) observaram perda da massa muscular do adutor do polegar significativa somente em idosos quando submetidos à imobilização dessa musculatura, sendo que no mesmo estudo os autores puderam constatar redução da força muscular de forma semelhante nos dois grupos, atribuindo desta forma a compensação da atrofia aos fatores neurais. Somado a isso, o processo de perda de força tem sido atribuído em grande parte ao declínio de MM característico do envelhecimento.…”
Section: Discussionunclassified